Relationship between antioxidant properties and GC-MS component composition of extracts from flowers, leaves and fruits of Crataegus Oxycanta - Hadjimitova, Vera (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
The aim of this study was to perform a comparative investigation of the antioxidant effect of Crataegus oxycanthas’ flowers, leaves, green and ripe fruits probes and to relate the obtained results with the ones of the accomplished qualitative GC-MS analysis of the antioxidant components participating in the studied standardized ethanol extracts. We established that the three extracts have well manifested antioxidant properties in three biological relevant model systems with different mechanism of generation of ROS: Fe-induced lipid peroxidation, UV induced deoxyribose damage and horse-radish peroxidase (HRP)-H2O2 chemiluminescent system. In the UV system the strongest effect is observed for the extract from flowers and leaves (C-50 = 0.109±0.009 mg/ml), followed by the ones from ripe fruits (C-50 = 0.259±0.015 mg/ml) and finally – by green fruits (C-50 = 0.557±0.014 mg/ml). In the Fe-induced lipid peroxidation system the antioxidant effect of the studied samples decreases in the following order: effect of flowers and leaves (C-50 = 0.287±0.018 mg/ml) > effect of green fruits (C-50 = 0.495±0.021 mg/ml) > effect of ripe fruits (C-50 = 0.704±0.035 mg/ml). Similar results were obtained in the HRP-H2O2 system. The generalized results show that the strongest antioxidant effect is observed for the plant extract from flowers and leaves of Crataegus. The GC-MS analyses we carried out indicate that the observed differences are due to the presence of a bigger number of constitutes possessing antioxidant properties in flowers and leaves extracts, compared with the fruits extracts.